Factors and forms of migration in the Eurasian migration system - Iskakov I.М. (Bulletin of the Karaganda University “Law Series”, 2019)
The article is intended for a comprehensive analysis of global problems of classification and regulation of migration. The problem of migration in the world is notable for its complexity. The reason is that, besides le-gal issues, political economic, demographic and social problems, both ethnographic and economic problems of human resources are relevant. The legal aspect has a special place. The legal branch plays a crucial role in the legal regulation of the migration process and its regulation. The change in the age structure of the popula-tion of the CIS countries is associated with the problem of aging. In the vast majority of countries in the post-Soviet space, the proportion of people of retirement age will increase, as well as the proportion of youth and working-age population will decline. This process will be especially intensive in Ukraine, Russia, Moldova, Georgia and Armenia. An increase in the share of pensioners in the total population will be fraught with an increase in pension burdens and an increase in the expenditures of states for pension payments, health care and social expenditures. At present, a stable migration subsystem has emerged between Russia, Kazakhstan and the countries of Central Asia, which is characterized by large-scale migration flows and a steady geographical orientation.